KERAGAMAN SEKUEN GEN NRPS 14 ISOLAT ACTINOMYCETES LAUT YANG BERPOTENSI MENGHASILKAN SENYAWA ANTIKANKER - , Shinta Hartanto; , Dr. Jaka Widada, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Marine actinomycetes is a group of bacteria that has highly potential to produce novel bioactive compound. They have unique characteristics and different from the terrestrial ones. Extreme environmental condition suspected to be lead marine actinomycetes produce different types of bioactive compound which has been found previously. This study aims to determine the NRPS gene sequence diversity of 14 marine actinomycetes that showed anticancer activity previously. Analysis of NRPS gene sequence diversity conducted by PCR RFLP (restriction fragmen length polymorphism) with HaeIII restriction enzyme digestion and followed by sequencing. The result of NRPS gene sequence diversity in 14 marine actinomycetes isolates indicated by four different DNA restriction patterns and can be devided in to 4 groups. Group A consisted of GMY01